Regulation of Endoplasmic Reticulum–Mitochondria Ca2+ Transfer and Its Importance for Anti-Cancer Therapies - Pedriali, Gaia; Rimessi, Alessandro; Sbano, Luigi; Giorgi, Carlotta; Wieckowski, Mariusz R.; Previati, Maurizio; Pinton, Paolo (Frontiers in Oncology, 2017)
Inter-organelle membrane contact sites are emerging as major sites for the regulation of intracellular Ca2+ concentration and distribution. Here, extracellular stimuli operate on a wide array of channels, pumps and ion exchangers to redistribute intracellular Ca2+ among several compartments. The resulting highly defined spatial and temporal patterns of Ca2+ movement can be used to elicit specific cellular responses, including cell proliferation, migration or death. Plasma membrane also can directly contact mitochondria and endoplasmic reticulum through caveolae, small invaginations of the plasma membrane that ensure inter-organelle contacts, and can contribute to the regulation of numerous cellular functions through scaffolding proteins such as caveolins. Plasma membrane and endoplasmic reticulum organize specialized junctions. Here, many components of the receptor-dependent Ca2+ signals are clustered, including the Orai1-STIM1 complex. This complex constitutes a primary mechanism for Ca2+ entry into non-excitable cells, modulated by intracellular Ca2+. Several contact sites between the endoplasmic reticulum and mitochondria, termed mitochondria-associated membranes, show a very complex and specialized structure and host a wide number of proteins that regulate Ca2+ transfer. In this review, we summarize current knowledge of the particular action of several oncogenes and tumor-suppressors at these specialized check points and analyze anticancer therapies that specifically target Ca2+ flow at the inter-organelle contacts to alter the metabolism and fate of the cancer cell.